Pengaruh Partisipasi Masyarakat terhadap Perencanaan Pembangunan dalam Forum Musrenbangdes di Desa Pondok, Kecamatan Babadan, Kabupaten Ponorogo - Qonita Fimelia; Muhammad Farid Ma’ruf; Galih Wahyu Pradana; Firre An Suprapto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Effective village development through the Village Development Planning Consultative Forum (MusrenbangDes) relies heavily on active community involvement, ensuring that planned programs reflect their needs and expectations. This study aimed to determine the effect of community participation on village development planning in Pondok Village, Babadan District, Ponorogo Regency. Data were collected through questionnaires distributed to 84 respondents and analyzed using simple linear regression. A quantitative approach was used as the survey method. The results showed that community participation and village development planning were quite good. With a Cronbach's Alpha value of 0.889, validity and reliability tests indicated that the instrument was valid and reliable. The relationship between variables was linear, normally distributed, and no heteroscedasticity was found in the classical assumption test. Simple linear regression results indicated that community participation had a significant influence on village development planning. With regression coefficient of 0.787 and a significance value of p < 0.001, community participation was responsible for 53.1% of the variation in village development planning. This is shown by the coefficient of determination (R²) of 0.531. Therefore, to improve village development plans through MusrenbangDes, community participation is crucial. Village governments must prioritize increasing sustainable participation at each stage of the planning process.